An adjustable force soft-contact lithography for patterning biomolecules on 3D topologies - Wan Salim, Wan Wardatul Amani; Humad, Shweta; Ayazi, Farrokh; Ziaie, Babak (IEEE, 2005)
In this paper, we report on a precision patterning technique using an adjustable-force soft-landing contact lithography that can be used to stamp functional biomolecules on planar and non-planar fragile surfaces. We have successfully patterned fluorescent antibodies (Alexa 568 antigoat IgG) on high frequency silicon microresonators with central vibrating bodies ranging from 20x10 to 480x240pm2 and arrays of 40pm diameter circular patterns with superior uniformity and without loss in proteins functionality. The printed antibodies were tested for effectiveness in binding fluorescent conjugated antigen (488 labeled goat anti-mouse IgG), and were shown to retain nearly-optimal bindings.